pygeodyn 1.1.0: a Python package for geomagnetic data assimilation - Huder, Loïc; Gillet, Nicolas; Thollard, Franck (Geoscientific Model Development, 2019)
The pygeodyn package is a sequential geomagnetic data assimilation tool written in Python. It gives access to the core surface dynamics, controlled by geomagnetic observations, by means of a stochastic model anchored to geodynamo simulation statistics. The pygeodyn package aims to give access to a user-friendly and flexible data assimilation algorithm. It is designed to be tunable by the community by different means, including the following: the possibility to use embedded data and priors or to supply custom ones; tunable parameters through configuration files; and adapted documentation for several user profiles. In addition, output files are directly supported by the package webgeodyn that provides a set of visualization tools to explore the results of computations.